(untitled) (Al-Qamar, 2023)
Culture is a broad term which is defined and interpreted by different scholars in different ways. In general, culture is defined as the national heritage which reflects the collective thinking of a nation. And it is practically depicted in the lifestyle of a non-homogenous society. It is a ground-based reality that the culture does not come into existence before due period of time. Rather it evolves again and again with the passage of time. And there are too many factors that contribute to the genesis of cultural norms. Moreover, the instrument of culture is not only a combination of mere norms, common practices, and conventions, rather it is something more than that. It shows how a nation has passed through an evolutionary process. And how it reacted to the timely impending cultural challenges and deconstructions. Hence, culture is the collective inheritance of a nation, which by choice or by default gets transferred to the upcoming generations.